Different positions in society, differing views of the world: the privatization of water and sanitation services in Minas Gerais, Brazil - Neves-Silva, Priscila; Braga, Juliana Gontijo; Heller, Léo (Frontiers in Sustainable Cities, 2023)
Introduction In 2020, the Brazilian government sanctioned Law No. 14.026, which established new guidelines for water and sanitation in the country and encouraged service privatization. Based on this, the State of Minas Gerais government, Brazil has proposed a bill for these services. Regarding this bill, different social actors in the State of Minas Gerais have expressed different assessments concerning the outcomes of the proposed management model and its impact on the realization of the human rights to safe water and sanitation. Methods We used content analysis techniques to assess the position of different actors—government, civil society, and private sector—in three public events that were recorded and posted on the YouTube platform. Results The analyses of this study indicated that the positions of the current government are aligned with those of the private sector. Also, the analyses agree that privatization can lead to the universalization of access to services. These different actors did not mention the human rights to safe water and sanitation in their discourses. Civil society organizations are concerned about the guarantee of those rights. For them, privatization of water and sanitation services can lead to discontinuation of the access of these services to vulnerable populations and poor municipalities due to tariff increases. Discussion The discourses concerning water and sanitation privatization as an instrument for universalization are disputed. Private sector actors and government representatives, aligned with the neoliberal agenda, support privatization. Civil society organizations defend the improvement of public management as the path to universalization. Representatives of municipalities were not included in the discussion for the new bill. The different societal positions relate to the different views these actors have concerning privatization and the world.